Nadir kay sat ankh macholi - Maryam, Shera; Shireen, Syed (book group Karachi, 1998)
Nadir Kay Sat Ankh Macholi (Hide and Seek with Nadir) is likely a children's story in Urdu that involves a game of hide-and-seek with the character Nadir. The story could be filled with excitement and suspense as Nadir hides in various creative and unexpected places. It might also highlight the importance of friendship, teamwork, and the joy of playing together.